Standardization as a Condition of Ensuring Quality and Safety of Production in the Uniform Markets of Integration Groups (on the Example of Russia and Other Countries of EEU) - Elena Anatolyevna Erasova; Vladimir Aleksandrovich Plotnikov (Управленческое консультирование, 2018)
Economic integration of Russia with other countries, despite in general successful development, faces a number of obstacles. One of them is insufficient coherence of national systems of technical regulation that generates risks for steady and economically safe development of Russia and the partner countries. In the article the approaches directed to increase in efficiency of cooperation of the countries of he Eurasian Economic Union in standardization, ensuring quality and safety of production in the uniform market are considered.